2017
DOI: 10.1186/s13568-017-0465-3
|View full text |Cite
|
Sign up to set email alerts
|

A two-stage temperature control strategy enhances extracellular secretion of recombinant α-cyclodextrin glucosyltransferase in Escherichia coli

Abstract: The effects of temperature on extracellular secretion of the α-cyclodextrin glucosyltransferase (α-CGTase) from Paenibacillus macerans JFB05-01 by Escherichia coli were investigated. When protein expression was induced at constant temperature, the greatest amount of extracellular recombinant α-CGTase was produced at 25 °C. Higher or lower induction temperatures were not conducive to extracellular secretion of recombinant α-CGTase. To enhance extracellular secretion of α-CGTase by E. coli, a two-stage temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…As shown in Table 2 , the maximum biomass at different temperatures of 24, 26, 28, 30, and 32°C was 28, 32, 30, 34, and 35%, respectively, which indicated that high temperature (30°C) with the highest AmB titer (11.01 g/L) could accelerate cell growth. In particular, we postulated that some enzymes associated with AmB biosynthesis, such as ketoreductase, cytochrome P450 enzymes, etc., may have higher optimum temperatures and promoted product synthesis by affecting the activity of related enzymes, which was consistent with other studies (Peng et al, 2010 ; Li et al, 2017 ). Furthermore, when the temperature exceeded 30°C, the cell growth was continuous, but the biosynthesis of AmB was essentially inhibited ( Table 2 ).…”
Section: Resultssupporting
confidence: 92%
“…As shown in Table 2 , the maximum biomass at different temperatures of 24, 26, 28, 30, and 32°C was 28, 32, 30, 34, and 35%, respectively, which indicated that high temperature (30°C) with the highest AmB titer (11.01 g/L) could accelerate cell growth. In particular, we postulated that some enzymes associated with AmB biosynthesis, such as ketoreductase, cytochrome P450 enzymes, etc., may have higher optimum temperatures and promoted product synthesis by affecting the activity of related enzymes, which was consistent with other studies (Peng et al, 2010 ; Li et al, 2017 ). Furthermore, when the temperature exceeded 30°C, the cell growth was continuous, but the biosynthesis of AmB was essentially inhibited ( Table 2 ).…”
Section: Resultssupporting
confidence: 92%
“…However, the temperatures required for microbial growth and product formation differ in most cases [ 14 ]. A phased temperature control strategy can provide ideal temperatures for both cell growth and product synthesis and is widely used in generating fermentation products such as α-cyclodextrin glucosyltransferase [ 27 ], 1,3-propanediol [ 14 ], and glutathione [ 28 ].…”
Section: Discussionmentioning
confidence: 99%